Omar Galliani : Turning Point by. - Palacio Foz Lisboa (Milano : Edizioni Charta Milano, 2000)
A magical journey trough poetry, sounds, words, writing, graphics, images, voices, memories and metaphors : light, shadow, water, fire, graphite, gold, men and fragments of man, poplars and the pulp of poplars, plants, animals - a fertile ground, a vital organism that lives the spirit of the times, of our time. The refined and passionate language through which Omar Galliani recounts the Mantras and his own experience of Art and beyond, sending out his message for the great turning point.
bibliog. p. 122-123
biog. [1 p.] (achterflap)
biog., ind. tent, gr. tent. p. 120-122
Engels
Italiaans
Turning Point by = Il Punto di Svolta di Omar Galliani, Palácio Foz Lisboa, 4-30 ottobre 2000
Keywords: Galliani, Omar